Barriers to healthcare for people on the autism spectrum. Issue 1 (4th January 2016) - Dern, Sebastian; Sappok, Tanja
Abstract : Purpose: – Adults on the autism spectrum experience difficulties in receiving health care, and health care providers face difficulties in offering health care to adults on the autism spectrum. The purpose of this paper is first, to assess the various difficulties and second, to provide strategies to overcome them. Design/methodology/approach: – In this qualitative research project, current barriers and facilitators to health care services were sampled from a collaboration of autistic self-advocates and autism professionals in Berlin, Germany. The findings were complemented by a review of practical guidelines and research about the service accessibility of patients on the autism spectrum. Findings: – A comprehensive list of barriers to health care was compiled and structured according to various aspects, such as "making appointments", "waiting area", "communication", and "examination". Strategies considering the perceptual and communicative peculiarities of autism were found to improve access to health care for autistic adults. Practical implications: – Providing access to the health care system may improve the diagnosis and treatment of mental and somatic illnesses, and thereby, the health status and quality of life for people on the autism spectrum. This recognition of the needs of adults on the autism spectrum may serve as a model for other areas in society, such as education and employment. Originality/value: – Data acquisition in this project is of special value because it resulted from collaboration between an autistic self-advocacy organization and professionals working in the field of intellectual developmental disabilities considering the experiences of autistic adults in the entire range of intellectual functioning.